Putting ASEAN to Test: The Roles and Challenges of Resolving the Myanmar Political Crisis After the 2021 Coup - Sirijintana, Worrawit (Graduate Review of Political Science and Public Administration Journal, 2022)
The 2021 Myanmar coup has created an opportunity for ASEAN to discard its longstanding non-interference principle. However, despite several attempts to solve the impasse, ASEAN has not delivered notable progress, calling into question the challenges that ASEAN faces in tackling the Myanmar impasse following the 2021 coup. As such, this paper aims to explain those challenges and how they contribute to the ineffectiveness of ASEAN in responding to Myanmar’s political crisis. Through documentary research utilizing secondary data, it further suggests that ASEAN work to overcome its challenges and act together to solve the crisis. From the framework developed in Noel Morada’s paper (2021), which proposes three factors that have contributed to ASEAN’s ineffectiveness during the Rohingya crisis, namely 1) constructive engagement, 2) accountability for atrocities, and 3) strategic considerations; this paper argues that although ASEAN has moved beyond its non-interference principle in the case of Myanmar’s post-2021 coup political crisis, it has struggled to maintain its centrality in Southeast Asia. ASEAN’s inability to effectively pressure Myanmar’s junta derives from three challenges: 1) the different degrees of adherence to the non-interference principle among member states, 2) the absence of regional accountability mechanisms and sanctions against member states, and 3) ASEAN’s strategic interests vis-à-vis great powers’ growing influence in Myanmar. Therefore, it is recommended that ASEAN and its member states consider 1) initiating a new mode of engagement in the ASEAN Charter to officially move beyond the principle of non-interference, 2) enhancing ASEAN’s regional accountability, including sanctions and punishments, in order to maintain collective action, and 3) developing its pivotal role in Southeast Asia through the establishment of more effective communication channels with the Tatmadaw.